2021
DOI: 10.3389/fonc.2021.681406
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Habitual Alcohol Intake With the Prognostic Significance of Mean Corpuscular Volume in Stage II-III Colorectal Cancer

Abstract: ObjectiveTo elucidate the prognostic significance of mean corpuscular volume (MCV), with implications of habitual alcohol intake in stage II-III colorectal cancer (CRC).BackgroundMCV had the potential to become an ideal prognostic biomarker and be put into clinical application. Few studies, however, have explored whether habitual alcohol intake which greatly increased the value of MCV would affect the prognostic role of MCV.MethodsEligible patients were identified from the CRC database of Fudan University Shan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…Those with high MCV levels before treatment had significantly shorter OS than those with low MCV levels. Similarly, we found that both T and N stages were negatively correlated with OS, which concurred with the results of previous studies ( 6 - 10 , 17 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those with high MCV levels before treatment had significantly shorter OS than those with low MCV levels. Similarly, we found that both T and N stages were negatively correlated with OS, which concurred with the results of previous studies ( 6 - 10 , 17 , 18 ).…”
Section: Discussionsupporting
confidence: 93%
“…Except for being used to assist in the diagnosis of hematological diseases, MCV has been reported as clinically associated with tumors such as head and neck tumors, esophageal cancer, colorectal cancer, liver cancer, etc. and a high MCV is a poor predictor of long-term survival in patients with solid tumors (6)(7)(8)(9)(10)17,18).…”
Section: Discussionmentioning
confidence: 99%
“…In general, SMYD4 negatively weak correlates with other SMYD genes. For instance, SMYD3 is known to be upregulated in colorectal cancers [ 24 , 25 , 26 , 27 ]. In patients with high expression of SMYD3 , SMYD4 is consistently downregulated, exhibiting a clear negative correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative malnutrition has been reported to be a predictor of outcomes in cancer patients and can be used as a prognostic indicator (15-17). Recently, MCV has been found to be another nutrition parameter correlated with the survival of various solid malignancies (3)(4)(5)(6)(7)(8). Previous studies showed that elevated MCV was always observed in patients with malnutrition due to alcohol abuse (3).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated MCV is always associated with deficiency of folate and vitamin B12, which may be seen in patients with a history of gastrectomy, malnutrition due to alcohol abuse, and so on (3). Recently, MCV was found to be correlated with the survival of patients with several malignancies, such as liver cancer, gastroesophageal adenocarcinomas, colorectal cancer, and head and neck cancer (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%